APLIKASI MANAJEMEN RISIKO BENCANA ALAM DALAM PENATAAN RUANG KABUPATEN NABIRE - widiati, ati (Badan Pengkajian dan Penerapan Teknologi, 2008)
Earthquakes happened at 7.6 (February 6th, 2004) and 8.1 (November 26th, 2004) scale of Richter in Nabire Regency had been implicating that risk management of natural disaster are needed to complete the spatial planning arrangement. Thisearthquakes had damaged infrastructures and changed the land use, the spatial structure, and the social activities. This paper describes how the risk management of natural disaster applicated as one of components in spatial planning in order to prevent and minimize the dangerous, and also to minimize the risks and damaged of natural disaster.